Downlink capacity of interference-limited MIMO systems with joint detection. - Huaiyu Dai
The capacity of downlink cellular multiple-input multiple-output (MIMO) systems, where co-channel interference is the dominant channel impairment, is investigated in this paper, mainly from a signal-processing perspective. Turbo space-time multiuser detection (ST MUD) is employed for intracell communications and is shown to closely approach the ultimate capacity limits in Gaussian ambient noise for an isolated cell. Then, it is combined with various multiuser detection methods for combating intercell interference. Among various multiuser detection techniques examined, linear minimum-mean-square-error (MMSE) MUD and successive interference cancellation are shown to be feasible and effective. Based on these two multiuser detection schemes, one of which may outperform the other for different settings, an adaptive detection scheme is developed, which together with a Turbo ST MUD structure offers substantial performance gain over the well-known V-BLAST techniques with coding in this interference-limited cellular environment. The obtained multiuser capacity is excellent in the high to medium signal-to-interference ratio scenario. Nonetheless, numerical results also indicate that a further increase in system complexity, using base-station cooperation, could lead to further significant increases of the system capacity. The asymptotic multicell MIMO capacity with linear MMSE MUD preprocessing is also derived, and this analysis agrees well with the simulation results.
Keywords: Gaussian ambient noise; MMSE; V-BLAST techniques; Base-station cooperation; Cellular systems; Cochannel interference; Coding; Downlink capacity; Intercell interference; Interference cancellation; Interference-limited MIMO systems; Intracell communications; Joint detection; Minimum mean square error; Multiple input multiple output; Signal processing; Signal-to-interference ratio; Space-time multiuser detection; Turbo processing